The impact of chorionicity on pregnancy outcome and neurodevelopment at 2 years old among twins born preterm: the EPIPAGE‐2 cohort study. (12th March 2020) - Tosello, B; Garbi, A; Blanc, J; Lorthe, E; Foix‐L'Hélias, L; D'Ercole, C; Winer, N; Subtil, D; Goffinet, F; Kayem, G; Resseguier, N; Gire, C; et al.
Abstract : Objective: To compare the short‐ and mid‐term outcomes of preterm twins by chorionicity of pregnancy. Design: Prospective nationwide population‐based EPIPAGE‐2 cohort study. Setting: 546 maternity units in France, between March and December 2011. Population: A total of 1700 twin neonates born between 24 and 34 weeks of gestation. Methods: The association of chorionicity with outcomes was analysed using multivariate regression models. Main outcome measures: First, survival at 2‐year corrected age with or without neurosensory impairment, and second, perinatal, short‐, and mid‐term outcomes (survival at discharge, survival at discharge without severe morbidity) were described and compared by chorionicity. Results: In the EPIPAGE 2 cohort, 1700 preterm births were included (850 twin pregnancies). In all, 1220 (71.8%) were from dichorionic (DC) pregnancies and 480 from monochorionic (MC) pregnancies. MC pregnancies had three times more medical terminations than DC pregnancies (1.67 versus 0.51%, P  < 0.001), whereas there were three times more stillbirths in MC than in DC pregnancies (10.09 versus 3.78%, P  < 0.001). Both twins were alive at birth in 86.6% of DC pregnancies compared with 80.0% among MC pregnancies ( P  = 0.008). No significant difference according to chorionicity was found regarding neonatal deaths and morbidities. Likewise, for children born earlier than 32 weeks, the 2‐year follow‐up neurodevelopmental results were not significantly different between DC and MC twins. Conclusions: This study confirms that MC pregnancies have a higher risk of adverse outcomes. However, the outcomes among preterm twins admitted to neonatal intensive care units are similar irrespective of chorionicity. Tweetable abstract: Monochorionicity is associated with adverse perinatal outcomes, but outcomes for preterm twins are comparable irrespective of their chorionicity. Tweetable Abstract: Monochorionicity is associated with adverse perinatal outcomes, but outcomes for preterm twins are comparable irrespective of their chorionicity.